Fenomena Poligami Dalam Pergolakan Batin Perempuan Dalam Perspektif Islam - Mubakirah, Fadliah (Musawa: Journal for Gender Studies, 2017)
Marriage is a way to get legalization of relationship between a man and a woman, in point of religion or national law. Polygamy is a system or marriage form which someone has more than a wife. In Islam, polygamy is allowed but with tight conditions, which have to appropriate with the objective of marriage, to achieve happy family, sakinah mawaddah warahmah. How If someone who wants to do polygamy but didn’t qualified, the motive just because of sex desire. Islam doesn’t talk about halal and haram only but also pay attention to morality and ethics aspect. Polygamy is allowed but has to done with moral, the focus in this case is the feelings of women and their children, no-one is persucated, so the objective of marriage is achieved.